A Review of Orthodontic Expert Systems - M. Okan Akçam (Galenos Yayinevi, 2007)
The aim of the current study was to introduce a review on orthodontic expert systems. Particularly, in the recent years there is an increase in digital technology to be involved in all scientific fields and it is obvious that orthodontics can not be distant from the digital era. In addition, many factors and measurements are involved in evaluating the malocclusions, as a result of the development of diagnostic methods therefore orthodontic treatment planning process turn into a more complex course. The orthodontic expert systems are based on the logic that a lot of patient data is asessed by the help of computer programs and a treatment plan is presented to the clinician. In the current study, the developmental course and importance of expert systems in the orthodontic field has been presented, which is a gradually expanding method in medical and dental specialties.